Whole‐exome sequencing of transforming oral lichen planus reveals mutations in DNA damage repair and apoptosis pathway genes. (1st March 2022) - Xie, Fangyi; Gleue, Casey A.; Deschaine, Maria; Dasari, Surendra; Lau, Julie S.; Sartori‐Valinotti, Julio C.; Meves, Alexander; Lehman, Julia S.
Abstract: Background: Oral lichen planus confers a 1% risk of transformation to oral squamous cell carcinoma. While prior exome sequencing studies have identified multiple genetic mutations in oral squamous cell carcinoma, mutational analyses of lichen planus‐derived OSCC are lacking. We sought to clarify genomic events associated with oral lichen planus transformation. Methods: Using rigorous diagnostic criteria, we retrospectively identified patients with non‐transforming oral lichen planus (i.e., known to be non‐transforming with 5 years of clinical follow‐up; n  = 17), transforming oral lichen planus (tissue marginal to oral squamous cell carcinoma, n  = 9), or oral squamous cell carcinoma arising in lichen planus ( n  = 17). Gene mutational profiles derived from whole‐exome sequencing on fixed mucosal specimens were compared among the groups. Results: The four most frequently mutated genes in transforming oral lichen planus and oral squamous cell carcinoma (TP53, CELSR1, CASP8, and KMT2D) identified 12/17 (71%) of oral squamous cell carcinomas and 5/9 (56%) of transforming oral lichen planus but were absent in non‐transforming oral lichen planus. We identified other known oral squamous cell carcinoma mutations (TRRAP, OBSCN, and LRP2) but also previously unreported mutations (TENM3 and ASH1L) in lichen planus‐associated oral squamous cell carcinomas. Conclusions: These findings suggest alterations in DNA damage response and apoptosis pathways underlie lichen planus‐related oral squamous cell carcinoma transformation and are supported by mutational signatures indicative of DNA damage. This study characterized patterns of mutational events present in oral lichen planus associated with squamous cell carcinoma and in squamous cell carcinoma associated with oral lichen planus but not in non‐transforming oral lichen planus.